ANALISIS DETERMINAN GOOD GOVERNMENT GOVERNANCE SERTA IMPLIKASINYA PADA KUALITAS LAKIP - Danny Segara, Lalu (Program Studi Akuntansi FPEB UPI, 2017)
This study aimed to analyze the influence of morality, reliability, and commitment to the GGG and the implications on the quality LAKIP. The low performance of the apparatus in the delivery of LAKIP an inconsistency GGG that impact on the quality LAKIP. The population is involved in reporting apparatus LAKIP in thirteen units of the Ministry of Religious work throughout Central Lombok district. The sample is determined by purposive sampling method amounted to 50 respondents. analysis using SMART Partial Least Square (PLS) Version 2.0. Findings show GGG influenced by morality and reliability, but is not influenced by the commitment apparatus. Other findings indicate GGG has implications for the quality LAKIP. Implications of the study is useful as consideration of the leadership ranks of the Ministry of Religious Affairs, in optimizing GGG